2012
DOI: 10.1371/journal.pone.0032856
|View full text |Cite
|
Sign up to set email alerts
|

Presumed Symbolic Use of Diurnal Raptors by Neanderthals

Abstract: In Africa and western Eurasia, occurrences of burials and utilized ocher fragments during the late Middle and early Late Pleistocene are often considered evidence for the emergence of symbolically-mediated behavior. Perhaps less controversial for the study of human cognitive evolution are finds of marine shell beads and complex designs on organic and mineral artifacts in early modern human (EMH) assemblages conservatively dated to ≈100–60 kilo-years (ka) ago. Here we show that, in France, Neanderthals used ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(107 citation statements)
references
References 21 publications
5
99
0
3
Order By: Relevance
“…In view of the extensive evidence from the final Mousterian and the early EUP, it needs to be considered that the deposition and alterations of cave bear bones probably had cultural significance and exogrammatic meanings. Similarly, evidence of utilization of diurnal raptor parts in what seems to be symbolic behavior has recently been reported from the Middle Paleolithic of France and Italy (Morin and Laroulandie 2012) [131].…”
Section: Figuresupporting
confidence: 53%
“…In view of the extensive evidence from the final Mousterian and the early EUP, it needs to be considered that the deposition and alterations of cave bear bones probably had cultural significance and exogrammatic meanings. Similarly, evidence of utilization of diurnal raptor parts in what seems to be symbolic behavior has recently been reported from the Middle Paleolithic of France and Italy (Morin and Laroulandie 2012) [131].…”
Section: Figuresupporting
confidence: 53%
“…Over such large distances, the only "infl uence" that could have been exerted is that concerning the notion of "personal ornamentation" itself. However, in western Europe, Neandertal body painting and personal ornamentation have Middle Paleolithic beginnings and predate both the IUP/Emiran and the Châtelperronian by thousands of years (Soressi and d'Errico 2007 ;Zilhão et al 2010a ;Peresani et al 2011 ;Morin and Laroulandie 2012 ;Finlayson et al 2012 ).…”
Section: Grotte Du Rennementioning
confidence: 99%
“…While Recent African Origin views interpreted many innovations of the European Upper Paleolithic as a "Human Revolution" (Mellars and Stringer 1989 ) triggered by the immigration of modern humans, the new evidence credited many of those innovations to the Neandertals and showed that some had fi rst appeared in the preceding Middle Paleolithic. Among the latter is the use in body ornamentation of painted/perforated marine shells, large raptor feathers, and mineral pigments modifi ed as crayons or processed for the preparation of complex cosmetic recipes (Soressi and d'Errico 2007 ;Zilhão et al 2010a ;Peresani et al 2011 ;Morin and Laroulandie 2012 ;Finlayson et al 2012 ). It is also quite possible that Neandertals were the makers of the earliest known cave art, as suggested by the minimum age of 41.4 ± 0.6 ka (95.4 % probability interval) provided by U-series dating of calcite accretions covering geometric signs and hand stencils at the Spanish site of El Castillo (Cantabria; Pike et al 2012 ).…”
mentioning
confidence: 99%
“…Neanderthal symbolic behaviors are attested by pigments associated with marine shells from ~45-50ka in Murcia, S.E. Spain (Zilhao et al 2010), as well as evidence for ornamental use of raptor feathers from similar or earlier dates (Morin and Laroulandie 2012;Peresani et al 2010). Because the FCC strategy is driven by female reproductive stress associated with encephalization, we expect both lineages, our own ancestors in Africa and those of the Neanderthals in Eurasia, to adopt it.…”
Section: What About the Neanderthals?mentioning
confidence: 99%